Assessment of trace elements in the long-term banana cultivation field’s soil - Islam, Md Saiful; Islam, Md Towhidul; Ismail, Zulhilmi; Islam, Abu Reza Md Towfiqul; Khan, Rahat; Hasan, Fakhrul; Kabir, Md Humayun; Ezewudo, Bede Izuchukwu; Ibrahim, Khalid A.; Idris, Abubakr M. (Frontiers in Environmental Science, 2023)
This work firstly assessed the contamination of trace elements (Cr, Cu, Ni, As, Zn Cd, Mn, Fe, and Pb,) in soil and different tissues of the banana plant (Musa spp.), ecological risks of trace elements using various indices, and probable health risks using a chemometric approach. Soil and different tissues of banana plants were collected from banana fields around the industrial area of the capital of old Pundranagar (the earliest urban archaeological location), Bangladesh.Samples were digested by acid digestion and trace elements were measured by inductively coupled plasma spectrophotometer (ICP-MS). The concentration of Cr, Ni, Cu, As, Cd, Pb, Fe, Mn and Zn in soil ranged as 1.